Artistic Synthesis of National Values in Poetry (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Our national values and tradition are artisticalliy interorela in this article poet Salim Ashurs poems iritten in the national spirit uare anal yzed.